2007
DOI: 10.1088/0031-9155/52/10/007
|View full text |Cite
|
Sign up to set email alerts
|

The small-animal radiation research platform (SARRP): dosimetry of a focused lens system

Abstract: A small animal radiation platform equipped with on-board cone-beam CT and conformal irradiation capabilities is being constructed for translational research. To achieve highly localized dose delivery, an x-ray lens is used to focus the broad beam from a 225 kVp x-ray tube down to a beam with a full width half maximum (FWHM) of approximately 1.5 mm in the energy range 40-80 keV. Here, we report on the dosimetric characteristics of the focused beam from the x-ray lens subsystem for high-resolution dose delivery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…Both HSCs and MSCs are implicated in the repair of irradiation damage of distal epithelial through their mobilization in the circulation (15)(16)(17). In this study, we aimed to investigate how irradiation affects bone marrow stem cells and residing microenvironment directly or indirectly by using a unique Small Animal Radiation Research Platform (SARRP) built by the Department of Radiation Oncology at Johns Hopkins University, in which computed tomography (CT), X-ray, and irradiation are integrated into a single system (18). We found that irradiation damaged the bone marrow microenvironment for stem cells, and our findings suggest that prevention of the damage during radiation therapy will be helpful for the recovery of bone injury.…”
mentioning
confidence: 99%
“…Both HSCs and MSCs are implicated in the repair of irradiation damage of distal epithelial through their mobilization in the circulation (15)(16)(17). In this study, we aimed to investigate how irradiation affects bone marrow stem cells and residing microenvironment directly or indirectly by using a unique Small Animal Radiation Research Platform (SARRP) built by the Department of Radiation Oncology at Johns Hopkins University, in which computed tomography (CT), X-ray, and irradiation are integrated into a single system (18). We found that irradiation damaged the bone marrow microenvironment for stem cells, and our findings suggest that prevention of the damage during radiation therapy will be helpful for the recovery of bone injury.…”
mentioning
confidence: 99%
“…Several laboratories are addressing this issue by developing methods for more precise small animal radiation therapy, including groups at Johns Hopkins University, [4][5][6][7][8][9][10] Princess Margaret Hospital, 11 and Washington University. [12][13][14][15][16] Our group has previously developed a method for precision irradiation of small animals by adapting an existing small animal microCT scanner with an x-ray tube operating at 70-120 kVp using a variable-aperture collimator with an aperture range of 1-102 mm at isocenter.…”
Section: Introductionmentioning
confidence: 99%
“…One such system is the small animal radiation research platform (SARRP; Xstrahl Ltd, Surrey, United Kingdom), which incorporates cone-beam computed tomography (CBCT) imaging with delivery of radiation to a specific anatomic location in small animal, matching the clinical techniques in radiation therapy. 16 The SARRP comes with the additional benefit of a treatment planning system that can do image fusion, contouring, and dose-volume histogram calculations. Nevertheless, one advantage of our system is that it can be adapted according to the need and it is an example of alternate system configuration.…”
Section: Introductionmentioning
confidence: 99%